Crap detection 101 how to distinguish good and bad information online - Rheingold, Howard (O'Reilly Media, 2011)
"Today, anyone can create a slick website or a compelling argument via email and find lots of impressionable viewers who will believe every word. In this video, Howard Rheingold offers solid guidelines to help you determine whether the information you come across on the Web is legitimate or whether it's just plain crap. A respected author and journalist who's been involved with the Web and Internet since the beginning, Rheingold will show you how to detect urban legends, spam email, criminal hoaxes, and phishing exploits, and more."--Resource description page.
Title from title screen. - Imprint from resource description page (viewed June 30, 2011)
Keywords: Information literacy; Internet; Online social networks; Information networks -- Social aspects; Culture de l'information; Réseaux sociaux (Internet); Réseaux d'information; Aspect social; Information networks; Social aspects; Electronic videos